A single bout of exhaustive treadmill exercise increased AMPK activation associated with enhanced autophagy in mice skeletal muscle. (14th February 2022) - Wang, Ping; Li, Chun Guang; Zhou, Xian; Cui, Di; Ouyang, Ting; Chen, Weikai; Ding, Shuzhe
Abstract: Previous studies reported inconsistent findings on autophagy activation in skeletal muscles after acute exercise. In this study, we investigated the effect of a single bout of exhaustive treadmill exercise on AMPK and autophagy activations in mice gastrocnemius muscle in vivo. Male ICR/CD‐1 mice were randomly divided into the control and exercise groups. The later was subjected to a single bout of exhaustive treadmill exercise. Changes of AMPK, phosphorylation of AMPK Thr172 (pAMPK Thr172 ), and autophagy markers including Beclin1, LC3II/LC3I and p62 mRNA and protein expressions in gastrocnemius muscle at different times (0, 6, 12, 24 h) after the exercise were analysed by quantitative real‐time PCR and western blot. Our results demonstrated that a single bout of exhaustive treadmill exercise significantly induced AMPK content and AMPK activity at 0, 6 and 12 h after the exercise, and changed the expressions of autophagy markers at different time points in the recovery period, respectively. Moreover, we observed positive correlations between expressions of LC3II/LC3I ratio and pAMPK Thr172 or AMPK, and a negative correlation between expressions of p62 and AMPK or pAMPK Thr172 . In conclusion, a single bout of exhaustive treadmill exercise in mice caused a prolonged activation of AMPK and improved autophagy in the gastrocnemius muscle. The regulation of autophagic markers were related to enhanced AMPK activity. The findings indicate that acute exercise enhanced AMPK‐related autophagy activation may be the underlying molecular mechanism that regulates cellular energy metabolism during exercise.